2019
DOI: 10.1128/iai.00591-19
|View full text |Cite
|
Sign up to set email alerts
|

Potential Mechanisms of Mucin-Enhanced Acinetobacter baumannii Virulence in the Mouse Model of Intraperitoneal Infection

Abstract: Porcine mucin has been commonly used to enhance the infectivity of bacterial pathogens, including Acinetobacter baumannii, in animal models, but the mechanisms for enhancement by mucin remain relatively unknown. In this study, using the mouse model of intraperitoneal (i.p.) mucin-enhanced A. baumannii infection, we characterized the kinetics of bacterial replication and dissemination and the host innate immune responses, as well as their potential contribution to mucin-enhanced bacterial virulence. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…The importance of macrophages in host defense against A. baumannii infection has been confirmed in mouse and rat models of A. baumannii infection (Breslow et al, 2011b;Qiu et al, 2012;Tsuchiya et al, 2012;Bruhn et al, 2015;Harris et al, 2019a;Kang et al, 2020;Lee et al, 2020). Macrophages phagocytose and kill A. baumannii at the early stage of the infection before large numbers of neutrophils are recruited to the site of infection (Qiu et al, 2012;Bruhn et al, 2015).…”
Section: Macrophagesmentioning
confidence: 94%
See 4 more Smart Citations
“…The importance of macrophages in host defense against A. baumannii infection has been confirmed in mouse and rat models of A. baumannii infection (Breslow et al, 2011b;Qiu et al, 2012;Tsuchiya et al, 2012;Bruhn et al, 2015;Harris et al, 2019a;Kang et al, 2020;Lee et al, 2020). Macrophages phagocytose and kill A. baumannii at the early stage of the infection before large numbers of neutrophils are recruited to the site of infection (Qiu et al, 2012;Bruhn et al, 2015).…”
Section: Macrophagesmentioning
confidence: 94%
“…On the other hand, neutralization of endogenous IFN-γ or TNF-α by monoclonal antibodies showed no effect on the tissue bacterial burdens or inflammatory responses in A. baumannii-infected mice (Van Faassen et al, 2007). This result was perhaps not entirely surprising since later studies have shown that IFN-γ was not consistently elevated after A. baumannii infection (Van Faassen et al, 2007;Qiu et al, 2009aQiu et al, ,b, 2012Qiu et al, , 2016Harris et al, 2013Harris et al, , 2019a. Similarly, neutralization of endogenous CXCL1 had no effect on intraperitoneal A. baumannii infection in mice (Breslow et al, 2011a), despite the fact that CXCL1 is a key chemotactic factor for neutrophil recruitment and was consistently detected locally or systemically at early stage of A. baumannii infection (Van Faassen et al, 2007;Qiu et al, 2009aQiu et al, ,b, 2012Qiu et al, , 2016Harris et al, 2013Harris et al, , 2019a.…”
Section: Proinflammatory Cytokines and Chemokinesmentioning
confidence: 96%
See 3 more Smart Citations